IMPLEMENTASI AUDIT OPERASIONAL DALAM PRINSIP TRANSPARANSI DAN AKUNTABILITAS PADA KANTOR KELURAHAN BAURUNG KECAMATAN BANGGAE TIMUR KABUPATEN MAJENE - Warka Syachbrani; Sitti Mujahida Baharuddin (P3M STIEM BONGAYA, 2019)
This study aims to find empirical evidence of how the implementation ofOperational Audit on the Principles of Transparency and Accountability in Governmentagencies.Thisresearchusedtheobservationanddocumentationmethodorcontentanalysismethod. Research data collection was carried out at the apparatus of KelurahanBaurung, Kecamatan Banggae Barat, Kabupaten Majene. The results of this studyfounded that the existence of an operational audit in accordance with applicable auditstandards and in accordance with the operational audit stages, would be able to improvethe principles of transparency and accountability in realizing good governance in thepublicsector.